Variability in the surface temperature and melt extent of the Greenland ice sheet from MODIS. Issue 10 (30th May 2013) - Hall, Dorothy K.; Comiso, Josefino C.; DiGirolamo, Nicolo E.; Shuman, Christopher A.; Box, Jason E.; Koenig, Lora S.
Abstract [1] Satellite‐derived moderate‐resolution imaging spectroradiometer (MODIS) ice‐surface temperature (IST) of the Greenland ice sheet shows a positive trend and two major melt events from 2000 to present. IST increased by ~0.55 ± 0.44°C/decade, with the greatest increase (~0.95 ± 0.44°C/decade) found in northwestern Greenland where coastal temperatures and mass loss are also increasing and outlet glaciers are accelerating. IST shows the highest rates of increase during summer (~1.35 ± 0.47°C/decade) and winter (~1.30 ± 1.53°C/decade), followed by spring (~0.60 ± 0.98°C/decade). In contrast, a decrease in IST was found in the autumn (~−1.49 ± 1.20°C/decade). The IST trends in this work are not statistically significant with the exception of the trend in northwestern Greenland. Major surface melt (covering 80% or more of the ice sheet) occurred during the 2002 and 2012 melt seasons where clear‐sky measurements show a maximum melt of ~87% and ~95% of the ice sheet surface, respectively. In 2002, most of the extraordinary melt was ephemeral, whereas in 2012 the ice sheet not only experienced more total melt, but melt was more persistent, and the 2012 summer was the warmest in the MODIS record (−6.38 ± 3.98°C). Our data show that major melt events may not be particularly rare during the present period of ice sheet warming.